Development of a virtual power market model to investigate strategic and collusive behavior of market players - Shafie-khah, Miadreza; Parsa Moghaddam, Mohsen; Sheikh-El-Eslami, Mohamad Kazem (Energy policy, 2013)
In this paper, a virtual power market model is proposed to investigate the behavior of power market players from regulator's point of view. In this approach, strategic players are modeled in a multi-agent environment. These agents which are virtual representative of actual players forecast the prices and participate in the markets, exactly the same as real world situation. In addition, the role of ISO is encountered by using security constraint unit commitment (SCUC) and security constraint economic dispatch (SCED) solutions. Moreover, the interaction between market players is modeled using a heuristic dynamic game theory algorithm based on the supply function equilibria (SFE). In addition to the collusive behavior, using the proposed model, the short-term strategic behavior of players, which their effects will appear in long-term, can be simulated. The proposed model enables the market regulators to make decision before implementing new market rules with the confidence of their results. To represent the effectiveness of the proposed method, a case study including wind power plants is considered and the impact of various market rules on players’ behavior is simulated and discussed. Numerical studies indicate that simulating the strategic and collusive behavior prior to any change in the market rules is necessary. •A virtual power market model is proposed using a heuristic dynamic game theory.•The proposed model can simulate the behavior of market players in a certain period.•This model can evaluate the oligopoly, collusive and strategic behavior of players.•The price uncertainty and security constraint are considered.•Neglecting strategic behavior of players can cause adverse consequences.